2020
DOI: 10.3390/cancers12082192
|View full text |Cite
|
Sign up to set email alerts
|

First-Line Treatment for Primary Breast Diffuse Large B-Cell Lymphoma Using Immunochemotherapy and Central Nervous System Prophylaxis: A Multicenter Phase 2 Trial

Abstract: There are limited data from prospective controlled trials regarding optimal treatment strategies in patients with primary breast diffuse large B-cell lymphoma (DLBCL). In this phase 2 study (NCT01448096), we examined the efficacy and safety of standard immunochemotherapy and central nervous system (CNS) prophylaxis using intrathecal methotrexate (IT-MTX). Thirty-three patients with newly diagnosed primary breast DLBCL received six cycles of rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Several studies have also reported that the involvement of specific extranodal sites, such as the testis or the breast, is associated with a high rate of CNS relapse. [7][8][9][10][11][12][13] In addition, specific biological features, such as double-hit lymphoma or double-expressor lymphoma, have been identified as high-risk factors for CNS relapse. [14][15][16] To reduce the incidence of CNS relapse in high-risk patients, prophylactic IV high-dose methotrexate (HD-MTX) has been considered an alternative to intrathecal methotrexate, because recent data have shown that intrathecal prophylaxis provides insufficient benefit.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also reported that the involvement of specific extranodal sites, such as the testis or the breast, is associated with a high rate of CNS relapse. [7][8][9][10][11][12][13] In addition, specific biological features, such as double-hit lymphoma or double-expressor lymphoma, have been identified as high-risk factors for CNS relapse. [14][15][16] To reduce the incidence of CNS relapse in high-risk patients, prophylactic IV high-dose methotrexate (HD-MTX) has been considered an alternative to intrathecal methotrexate, because recent data have shown that intrathecal prophylaxis provides insufficient benefit.…”
Section: Introductionmentioning
confidence: 99%
“…Four patients relapsed in the CNS and 2 patients in the breasts. This study showed chemotherapy with rituximab and CNS prophylaxis without routine local radiation may be a sufficient approach (12).…”
Section: Definitive Diagnosis Is Based On Pathologic Featuresmentioning
confidence: 74%
“…The addition of rituximab to CHOP remains controversial and some studies have reported improved outcomes while most did not observe any benefit. [13][14][15]…”
Section: Discussionmentioning
confidence: 99%